Respuesta :
Answer:
x=5, y=6
Step-by-step explanation:
-6x + 6y = 6
If we divide this by 6 (which we can do because it is an equation), we can simplify this by a lot.
-6x + 6y = 6
-x + y = 1 <-- NEW EQUATION #1
We can also simplify -6x + 3y = -12 by dividing everything by 3.
-6x + 3y = -12
-2x + y = -4 <-- NEW EQUATION #2
Substitution is fairly easy for this problem.
Isolate the variable
-x + y = 1
y = x + 1
Now substitute (x+1) for where you see y in the second equation.
-2x + (x + 1) = -4
-x + 1 = -4
x = 5
Now substitute 5 for x.
-(5) + y = 1
y = 6